Gender Equality and the Revitalization of Japan's Society and Economy Under Globalization - Osawa, Mari (Washington, DC: World Bank, 2012)
The global financial crisis that began with the collapse of the subprime mortgage market in the United States spread to economies around the world at an astonishing pace. In Japan, as 2009 began, jobs and often homes were lost with a suddenness and on a scale previously unknown, leaving people at a loss as to where to turn. At a time when Japan's own societal sustainability was seen to be under increasing threat, an unprecedented degree of instability was laid bare throughout the globalized economy. At precisely this juncture, in the general election of 30 August 2009, the long-standing Liberal Democratic Party (LDP)-led coalition government was replaced by a Democratic Party of Japan (DPJ)-led government in an historic change of administration.